(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Employee Engagement has arisen as a basic driver of Business Achievement today. Engagement can fundamentally influence Employee Maintenance, Efficiency, and devotion. The review endeavors to explore the degree of Employee Engagement and its indicators among the Leader level employees of a presumed Banking and Insurance Agency in Andhra Pradesh, India. The examination depends on the essential information gathered from 200 employees on various boundaries connected with Employee Engagement and its possible predictors. The investigation presumed that the degree of employee engagement in the association is very palatable. Four Factors to be specific “Employee Welfare, Empowerment, Employee Growth, and Interpersonal Relationships” were viewed as the Employee Engagement Predictors.